GRN knockdown regulates the expression and alternative splicing of genes associated with aphasia-related diseases in PC12 cells - Xi, Yanling; Abuduxiku, Munire; Qu, Mei (Brain research, 2024)
[Display omitted] •GRN is significantly more highly expressed in PSA.•GRN knockdown is associated with changes in transcription levels and the occurrence of alternative splicing events.•GRN is involved in a variety of biological processes. Prior research has shown that granulin precursor (GRN, also termed PGRN) is closely linked to aphasia. However, there has been little research on the mechanism of action of GRN in post-stroke aphasia (PSA). In this study, RT-qPCR was used to identify variations in gene expression, while RNA sequencing (RNA-seq) was utilized to acquire transcriptional profiles. The Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases were employed for bioinformatics analysis. GRN was considerably more active in PSA subjects. After silencing the GRN, 197 transcripts had differential expression, and 237 alternative splicing events (ASEs) were substantially affected. The analysis of differentially expressed genes (DEGs) using GO and KEGG approaches showed that these genes have various molecular functions and are significantly enriched in metabolic signaling pathways. Regarding Alternative Splicing (AS), the GO and KEGG analyses revealed numerous functional genes involved in transcription and metabolism. The knockdown of GRN has been shown to be associated with alterations in transcription, metabolism, and ASEs, potentially impacting transcriptional and metabolic pathways through its involvement in AS. Furthermore, GRN knockdown is associated with nervous system disease-related gene transcription and AS processes, as well as its involvement in G protein-coupled receptor (GPCR) and wingless/integrated (Wnt) signaling pathways, which impact the initiation and resolution of PSA.